How to make our signs clear : C.S. Peirce and semiotics - Svantner, Martin. (Value Inquiry Book Series, 2017)
How to Make Our Signs Clear is the result of an international cooperation between European and Brazilian Peircean scholars (I. A. Ibri, E. Višňovský, C. Paolucci and others) and strives to dispel simplifications of Peirce´s semiotic as well as to collect various insights into it and into its consequences for philosophy, especially philosophy of language, pragmatism and epistemology. The central theme of this book is the notion of the sign as a specific triadic relational unit, treated from various perspectives and applied to various fields of philosophy: semeiotic knowledge grows up from the discussions, common interests and possible conflicts between the readers of Peirce´s works. This book does not offer a general overview of Peirce´s theory of signs, but rather various analyses of consequences of some capacities of his semiotic.